Areas of Economic as the Factor of Improvement Regional Competitiveness - Bulychev, Lev L.; Ivanova, Elena A.; Khominich, Irina P.; Gureva, Maria A.; Yekomasova, Daria Yu. (International Journal of Economics and Financial Issues, 2016)
The competition modern development explains the many processes of the economic activity in the region and the country. The increasing value in the state policy is gained by the regional competitiveness that becomes one of the important factors in development and region formation in interaction with partners. The region economy sphere possesses the development specific features of the available resources and potentials, and has the development policy of the innovative enterprises, companies and other organizations. All the inherent features and the economic development potentials allow qualifying a particular region as the most competitive. This article is devoted to the consideration of effective policy, growth major factors of competitive advantages of the Russian regions, their territory, socio - economic state and image. The special attention will be paid to the consideration of special (particular) economic zones of the state regions, clusters, their formation in the modern conditions of the world fluctuations of the economic space and political interaction. The main problems in the sphere of execution and introduction of these zones are opened. The most important directions of the realization productivity of SEZ and their further maturing, as a factor of the region competitive advantages growth, as well as all the Russian Federation territory, are described. Keywords: regional policy, efficiency, competitiveness, competition, special economic zones, cluster, state, region, market JEL Classifications: A11, G18, O40